Labeled container
Patent Information
- Application Number
- JP2023505612
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-10
- Filing Date
- 2022-03-09
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-03-09
AI Technical Summary
In-mold labels on resin containers are difficult to peel off by hand, posing a challenge for efficient recycling.
A labeled container design featuring a specific combination of resin materials for the adhesive surfaces and notch portions around the label, allowing for easy peeling by hand.
The design achieves sufficient adhesive strength while enabling easy peeling of the label, facilitating efficient recycling of the resin containers.
Smart Images

Figure 0007665010000003 
Figure 0007665010000004 
Figure 0007665010000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a labeled container. [Background technology]
[0002] As a label for a resin container molded using a mold, an in-mold label is used, which is adhered to the surface of the resin container by heat during molding. In order to increase the adhesive strength with the resin container, it is usually necessary to design the heat seal layer of the in-mold label according to the physical properties of the material of the container. For example, in the case of a polyethylene terephthalate (PET) resin container, a compound having a polar group is blended into the heat seal layer to increase the affinity with the PET resin. In addition, in order to increase the polarity of the surface of the heat seal layer, the surface is subjected to a plasma treatment under nitrogen (see Patent Document 1 and Patent Document 2).
[0003] On the other hand, from the viewpoint of environmental protection, recycling of plastics is actively carried out. For example, shrink labels are peeled off from used labeled resin containers, and the resin containers are recycled. On the other hand, in-mold labels that are integrated into resin containers are usually peeled off by immersing the labeled resin container in a high-temperature alkaline aqueous solution for several tens of minutes (for example, see Patent Document 3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2020 / 067327 [Patent Document 2] JP 2009-40038 A [Patent Document 3] JP 2006-168355 A Summary of the Invention [Problem to be solved by the invention]
[0005] Shrink labels can usually be peeled off by hand, but in-mold labels are difficult to peel off by hand. For this reason, an easier method for peeling off labels has been desired.
[0006] An object of the present invention is to provide a container with a label that has sufficient adhesive strength but can be easily peeled off when emptying the container. [Means for solving the problem]
[0007] As a result of intensive research conducted by the inventors to solve the above-mentioned problems, they discovered that the above-mentioned problems could be solved by using a specific combination of resin materials on the adhesive surfaces of the label and the resin container, and further designing the notch portion that occurs on the surface of the resin container around the label to a specific size, and thus completed the present invention. That is, the present invention is as follows.
[0008] (1) A labeled container comprising a label having a heat seal layer and a resin container to which the label is adhered via the heat seal layer, A part of the label is embedded in the resin container, and a notch is provided around the label. The depth (d) of the notch is 40 μm or more, The width (L) of the notch portion is 300 μm or more, One of the resin container and the heat seal layer at the adhesive surface contains a polyolefin resin as a main component, and the other contains a polyester resin as a main component. Labeled container.
[0009] (2) The depth (d) of the notch is 100 μm or less. A container with a label as described in (1) above.
[0010] (3) The width (L) of the notch is 900 μm or less. A container with a label according to (1) or (2) above.
[0011] (4) The heat seal layer contains a polyolefin resin as a main component, The resin container contains a polyester resin as a main component. A container with a label according to any one of (1) to (3) above.
[0012] (5) The label has a base layer on a surface of the heat seal layer opposite the resin container, The substrate layer is a porous resin film containing a thermoplastic resin and a filler. A container with a label according to any one of (1) to (4) above. Effect of the Invention
[0013] According to the present invention, it is possible to provide a container with a label that has sufficient adhesive strength but is easy to peel off when emptying the container. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2 is a plan view showing an example of a labeled container. [Diagram 2] FIG. 2 is a cross-sectional view of a labeled container. [Diagram 3] FIG. 3 is an enlarged view of the area enclosed by the dotted line in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The labeled container of the present invention will be described in detail below. The following description is an example (representative example) of the present invention, and the present invention is not limited thereto. In the following description, the term "(meth)acrylic" refers to both acrylic and methacrylic.
[0016] [Container with label] The labeled container of the present invention comprises a label having a heat seal layer and a resin container. The label is adhered to the resin container via the heat seal layer. A part of the label is embedded in the resin container, and a notch is provided around the label of the labeled container. The notch is formed by the embedded end of the label and the resin container surrounding the end of the label. Such a labeled container can be obtained by adhering the heat seal layer to the resin container by heat during molding of the resin container, and by allowing the molten resin of the container to conform to the shape of the label.
[0017] <Notch of resin container> In the present invention, the depth (d) of the notch, that is, the length (d) from the surface of the unlabeled resin container to the deepest part of the notch, is 40 μm or more. Moreover, the width (L) of the notch, that is, the length from the edge of the label to the outer edge of the notch, is 300 μm or more.
[0018] The notch of this size allows a fingernail or a plate-shaped tool to be inserted around the label, forming an opening for peeling off the label. For example, by inserting a fingernail into the notch and pressing it toward the label, the adhesive surface between the label and the resin container can be easily separated by hand. This makes it easier to recycle the resin container after the label has been peeled off, without having to go through a complicated process such as immersing it in an alkaline solution.
[0019] From the viewpoint of easiness in creating an opportunity to peel off the label, the depth (d) of the notch is preferably 50 μm or more, more preferably 60 μm or more, and from the same viewpoint, the width (L) of the notch is preferably 400 μm or more, more preferably 500 μm or more. From the viewpoint of avoiding practical problems such as the falling off of the label before ejection due to the notch, the depth (d) of the notch is preferably 100 μm or less, more preferably 90 μm or less, and from the same viewpoint, the width (L) of the notch is preferably 900 μm or less, more preferably 800 μm or less.
[0020] On the other hand, in a labeled container, a part of the label (a part in the thickness direction) is embedded in the resin container. This allows the label to be fixed to the resin container while leaving a notch that serves as a trigger for peeling off the label, making it easier to obtain practical adhesion when using the labeled container. From the viewpoint of adhesion, the embedding rate of the label in the resin container, calculated by the following formula (F1), is preferably 3% or more, more preferably 5% or more, even more preferably 10% or more, and particularly preferably 20% or more. From the viewpoint of ease of peeling, the embedding rate is preferably 50% or less, more preferably 30% or less. (F1) Embedment rate (%) = (td) × 100 / t (In formula (F1), t represents the thickness of the label (excluding the protruding portion if the label protrudes from the surface of the resin container), and d represents the depth of the notch.)
[0021] The size of the notch can be adjusted by the heating and pressurizing conditions during molding of the resin container.
[0022] <Resin container and label resin materials> In the present invention, one of the resin container and the heat seal layer at the adhesive surface contains a polyolefin resin as a main component, and the other contains a polyester resin as a main component. The main component refers to the resin component that is contained in the largest amount among various resins.
[0023] Usually, the same type of resin as the main component of the resin container is selected for the heat seal layer of the label. This is because the same type of resin has high affinity with each other and increases adhesion. For example, if the main component of the resin container is polyethylene resin, a polyolefin resin such as the same polyethylene resin is selected as the main component of the heat seal layer. Conversely, if the main component of the resin container is polyester resin such as PET resin, a resin having a polar group like PET resin can be selected as the main component of the heat seal layer.
[0024] However, in the present invention, when a polyolefin resin such as polyethylene resin is used as the main component of the resin container, a polyester resin is selected as the main component of the heat seal layer, and conversely, when the resin container side is a polyester resin, a polyolefin resin is selected as the main component of the heat seal layer. A combination of resin materials that are not the same type results in lower adhesion than a combination of the same types. Therefore, the label can be easily peeled off from the notch around the label by hand. In this way, by adjusting the adhesion to be low by material design, and by covering at least a part of the resin container with the label end and making the notch an appropriate size, a labeled container can be obtained that has no practical problems during use and is easy to peel off the label by hand when discharging.
[0025] A specific example will be described with reference to Figs. FIG. 1 shows the appearance of a labeled container 10 that is an example of the present invention. The labeled container 10 comprises a hollow resin container 1 and a label 2 adhered to its surface.
[0026] FIG. 2 is a cross-sectional view of the labeled container 10. The label 2 is embedded in the resin container 1, which is recessed inward due to the embedding. A notch 11 is formed in the labeled container 10 by the inner wall of the resin container 1, which is inclined due to the recess, and the outer wall of the end of the label 2. In other words, a gap is generated around the label 2 of the resin container 1.
[0027] As described above, the depth d of the notch portion 11 is 40 μm or more. The width L of the notch portion 11 is 300 μm or more. The depth d is measured as the distance between points P1 and P2, and the width L is measured as the distance between points P2 and P3. Point P1 is the intersection of the inclined surface K1 of the resin container 1 forming the notch portion 11 and the end surface of the label 2. Point P2 is the intersection of a line K3 extending in the thickness direction of the label 2 through the intersection P1 and a line K4 extending along the surface of the resin container 1 to which the label 2 is not attached. Point P3 is the intersection of the line K4 and the inclined surface K1 of the resin container 1.
[0028] FIG. 3 is an enlarged view of the area enclosed by the dotted line 100 in FIG. The label 2 includes a base layer 21 and a heat seal layer 22. The heat seal layer 22 is adhered to the surface of the resin container 1 by heating. A print layer 3 may be provided on the surface of the base layer 21 opposite the heat seal layer 22.
[0029] The structure of the labeled container will be described below. (Resin container) As described above, the resin material of the resin container of the present invention can be a polyester resin or a polyolefin resin. The resin container may have a single-layer structure or a multi-layer structure. In the case of a multi-layer structure, the outermost layer to be adhered to the label contains a polyester resin or a polyolefin resin as a main component.
[0030] Examples of polyester resins include polyethylene terephthalate (PET), polybutylene terephthalate, polybutylene succinate, and polylactic acid. Examples of the polyolefin resin include polypropylene-based resin and polyethylene-based resin.
[0031] The color of the container may be transparent or a natural color containing no coloring material such as a pigment or dye, or may be an opaque color obtained by applying a coloring material or coloring. The cross-sectional shape of the body of the container may be a perfect circle, an ellipse, or a rectangle. When the cross-sectional shape of the body is a rectangle, it is preferable that the corners have a curvature. From the viewpoint of strength, it is preferable that the cross-section of the body is a perfect circle or an ellipse close to a perfect circle, and it is more preferable that the cross-section is a perfect circle.
[0032] (label) The label of the present invention can be used as an in-mold label. The label is usually a laminate including a base layer and a heat seal layer, but may further include other layers as necessary. For example, as shown in FIG. 3, the label may include a printing layer on the surface of the base layer opposite to the heat seal layer. The printing layer is a layer made of an ink composition transferred by printing.
[0033] In addition to the printing layer, for example, pattern layers such as transfer foils, holograms, and security threads provided for purposes such as design and anti-counterfeiting, intermediate layers for adjusting thickness and strength, and functional layers such as polarizing films may be provided.
[0034] <Base material layer> The base layer is not particularly limited as long as it can impart strength to the label, and can be, for example, a thermoplastic resin film. From the viewpoint of obtaining a white label, the base layer may be a porous resin film containing a thermoplastic resin and a filler.
[0035] When a porous resin film is used, the label is pressed against the inner wall of the mold during in-mold molding. At this time, the pores in the porous resin film may be crushed, and the thickness of the base layer may become smaller. However, when the label is removed from the mold and released from the pressure, the pores in the porous resin film return to their original state, and the thickness of the base layer also returns to its original state. In the mold, the label and the surface of the resin container were at the same position due to the pressure, but the surface of the label protrudes from the surface of the resin container due to the increase in the thickness of the base layer. This makes it easier for a fingernail or the like to get caught in the notch of the resin container around the label, making it easier to form a trigger for peeling. In addition, in the case of a porous resin film, the cushioning property is likely to be strong, so that when the label is released from the blow pressure of in-mold molding, it rebounds and is less embedded in the resin container, making it easier to form a deep notch.
[0036] From the viewpoint of facilitating the formation of a peeling trigger, the base layer may be a stretched film containing a thermoplastic resin. When the base layer is a stretched film, the elastic modulus tends to be higher, so that the label rebounds when released from the blow pressure of in-mold molding, and is less embedded in the resin container, making it easier to form a deep notch.
[0037] Examples of thermoplastic resins that can be used for the substrate layer include polyolefin resins, polyester resins, polyvinyl chloride resins, polyamide resins, polystyrene resins, and polycarbonate resins. These can be used alone or in combination of two or more. From the viewpoint of mechanical strength, the substrate layer is preferably mainly composed of polyolefin resins or polyester resins, and more preferably mainly composed of polyolefin resins.
[0038] Examples of polyolefin resins that can be used for the base layer include polypropylene resins, polyethylene resins, etc. Among these, polypropylene resins are preferred from the viewpoints of moldability and mechanical strength.
[0039] Examples of polypropylene resins include propylene homopolymers such as isotactic homopolypropylene and syndiotactic homopolypropylene obtained by homopolymerizing propylene, and propylene copolymers obtained by copolymerizing propylene as a main component with α-olefins such as ethylene, 1-butene, 1-hexene, 1-heptene, 1-octene, and 4-methyl-1-pentene, etc. The propylene copolymer may be a binary system or a multi-component system of ternary or higher components, and may be a random copolymer or a block copolymer.
[0040] The polyethylene resin has a density of, for example, 0.940 to 0.965 g / cm 3 High density polyethylene, density is 0.920~0.935g / cm 3 Medium density polyethylene, with a density of 0.900 to 0.920 g / cm 3 Examples of such copolymers include linear low density polyethylene, copolymers mainly composed of ethylene and copolymerized with α-olefins such as propylene, butene, hexene, heptene, octene, and 4-methylpentene-1, and ethylene-cyclic olefin copolymers. Among the above polyolefin resins, one type may be used alone, or two or more types may be used in combination.
[0041] Examples of polyester resins that can be used for the substrate layer include polyethylene terephthalate resin, polybutylene terephthalate resin, and polyethylene naphthalate, etc. Examples of polyamide resins that can be used for the substrate layer include nylon-6, nylon-6,6, nylon-6,10, and nylon-6,12, etc.
[0042] (Filler) Fillers that can be used in the base layer include inorganic fillers and organic fillers. The inclusion of a filler makes it easier to form a porous resin film having pores inside the film. In addition, the whiteness or opacity of the base layer can be increased.
[0043] Examples of inorganic fillers include inorganic particles such as heavy calcium carbonate, light calcium carbonate, calcined clay, silica, diatomaceous earth, white clay, talc, titanium oxide such as rutile titanium dioxide, barium sulfate, aluminum sulfate, zinc oxide, magnesium oxide, mica, sericite, bentonite, sepiolite, vermiculite, dolomite, wollastonite, and glass fiber. Among them, heavy calcium carbonate, clay, and diatomaceous earth are preferable because they have good pore formability and are inexpensive. In addition, for the purpose of improving dispersibility, the surface of the inorganic filler may be surface-treated with a surface treatment agent such as a fatty acid.
[0044] When the thermoplastic resin constituting the base layer is mainly composed of a polyolefin resin, examples of the organic filler include organic particles such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polyamide, polycarbonate, polystyrene, cyclic olefin homopolymer, ethylene-cyclic olefin copolymer, polyethylene sulfide, polyimide, polymethacrylate, polyethyl ether ketone, polyphenylene sulfide, and melamine resin, which are incompatible with the polyolefin resin. The filler contained in the base layer may be one type of the above-mentioned inorganic fillers or organic fillers, or a combination of two or more types.
[0045] From the viewpoint of increasing the whiteness or opacity of the base layer, the content of the filler in the base layer is preferably 10% by mass or more, more preferably 15% by mass or more. From the viewpoint of increasing the uniformity of the molding of the base layer, the content of the filler in the base layer is preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less.
[0046] From the viewpoint of easiness of forming pores, the average particle size of the filler is preferably 0.01 μm or more, more preferably 0.05 μm or more, and even more preferably 0.1 μm or more. From the viewpoint of imparting mechanical strength such as tear resistance, the average particle size of the filler is preferably 15 μm or less, more preferably 5 μm or less, and even more preferably 2 μm or less.
[0047] The average particle diameter of the inorganic filler is the volume average particle diameter (cumulative 50% particle diameter) corresponding to 50% of the cumulative volume measured by a particle measuring device, for example, a laser diffraction type particle size distribution measuring device (Microtrac, manufactured by Nikkiso Co., Ltd.). The average particle diameter of the organic filler is the average dispersed particle diameter when dispersed in a thermoplastic resin by melt kneading and dispersion. The average dispersed particle diameter can be determined by observing a cut surface of a thermoplastic resin film containing an organic filler with an electron microscope, measuring the maximum diameter of at least 10 particles, and averaging the measured diameters.
[0048] Depending on the purpose, the base layer may contain additives such as antioxidants such as sterically hindered phenols, phosphorus-based, amine-based, and sulfur-based antioxidants; light stabilizers such as sterically hindered amines, benzotriazole-based, and benzophenone-based light stabilizers; dispersants; lubricants; and antistatic agents. The content of the additives in the base layer can usually be independently set to 0.001 to 3 mass % for each type of additive, from the viewpoint of obtaining a sufficient effect of the additives while suppressing a decrease in printability.
[0049] <Thickness> The thickness of the base layer is preferably 40 μm or more, more preferably 50 μm or more, from the viewpoint of suppressing the occurrence of wrinkles during printing, facilitating fixation at the desired position when inserted into the mold, and giving the label a trigger for peeling after ejection. Also, from the viewpoint of reducing the amount of resin used in the label, the thickness of the base layer is preferably 150 μm or less, more preferably 120 μm or less. Therefore, the thickness of the base layer is preferably 40 to 150 μm, more preferably 50 to 120 μm.
[0050] The substrate layer may have a single layer structure or a multilayer structure. In the case of a multilayer structure, each layer can impart various functions such as white opacity, adhesion to the ink used in the printing layer, heat insulation, and easy peelability.
[0051] Suitable transparent substrate layers include filler-free polypropylene-based unstretched films (CPP films), polypropylene-based biaxially oriented films (BOPP films), polyethylene terephthalate-based unstretched films (CPET films), and polyethylene terephthalate-based biaxially oriented films (BOPET films). In addition, suitable opaque base layers include CPP films, BOPP films, CPET films, BOPET films, and the like, each containing a filler.
[0052] The surface of the base layer may be activated by an activation treatment in order to enhance adhesion to the printing layer. Examples of the activation treatment include corona discharge treatment, frame treatment, plasma treatment, glow discharge treatment, and ozone treatment. Among these, corona discharge treatment or frame treatment is preferred, and corona treatment is more preferred.
[0053] From the same viewpoint, a printable layer may be provided between the substrate layer and the printing layer. The printable layer preferably contains at least one of a binder and an antistatic agent in order to enhance adhesion with the printing layer. The printable layer may also contain additives such as an antiblocking agent, a colorant, an antifoaming agent, and an antifungal agent, as necessary.
[0054] <Heat seal layer> The heat seal layer enhances the adhesiveness of the label to the resin container. During in-mold molding of the resin container, the label is placed inside the mold so that the resin container and the heat seal layer face each other. The heat during in-mold molding melts the heat seal layer, and the label adheres to the surface of the resin container.
[0055] As described above, the heat seal layer contains polyolefin resin or polyester resin as a main component in accordance with the resin used as the main component of the resin container surface. "Containing as a main component" means that the heat seal layer contains the resin in an amount of, for example, 50% by mass or more, preferably 70% by mass or more, and more preferably 90% by mass or more. Polyolefin resin is a resin containing only olefin as a polymerization component.
[0056] The heat seal layer containing a polyolefin resin as a main component may contain a resin having an olefin and a monomer having a polar group other than olefin as a polymerization component, as long as the effect of the present invention is not impaired. When the heat seal layer contains such a resin, the adhesiveness between the label and the polyester resin container can be improved, and the balance with the ease of peeling the label from the polyester resin resin container can be more accurately achieved. The resin having an olefin and a monomer having a polar group other than olefin as a polymerization component refers to a resin containing 50% by mass or more, preferably 70% by mass or more, more preferably 90% by mass or more of olefin as a polymerization component.
[0057] Examples of polyolefin resins that can be used in the heat seal layer include ethylene-based resins, propylene-based resins, ethylene-propylene copolymers, and ethylene-α-olefin copolymers. Examples of ethylene-based resins include those having a density of 0.900 to 0.935 g / cm 3 Low or medium density polyethylene, with a density of 0.880 to 0.940 g / cm 3Examples of such polyethylene resins include polyethylene resins having a melting point of 60 to 130° C., such as linear low-density polyethylene produced by using a metallocene catalyst, and metallocene-based polyethylene produced by using a metallocene catalyst. Of these, ethylene-based resins are more preferred, and low- or medium-density polyethylenes having a crystallinity of 10 to 60% measured by an X-ray method and a number-average molecular weight of 10,000 to 40,000, or linear low-density polyethylenes are preferred.
[0058] The polyester resin may be the same as the polyester resin exemplified as the main component of the resin container.
[0059] From the viewpoint of being sufficiently melted by heating during in-mold molding to enhance adhesiveness, the melting point of the resin used in the heat seal layer is preferably 130°C or lower, more preferably 110°C or lower, and even more preferably 100°C or lower.
[0060] The higher the melting point, the easier it is to form the film and the easier it is to reduce sticking to rolls during film production, so the melting point of the resin is preferably 45° C. or higher, and more preferably 50° C. or higher. The melting point can be measured by a differential scanning calorimetry (DSC).
[0061] Furthermore, the heat seal layer may contain additives commonly used in the polymer field, such as an anti-fogging agent, a lubricant, an anti-blocking agent, an antistatic agent, an antioxidant, a heat stabilizer, a light stabilizer, a weathering stabilizer, and an ultraviolet absorber, if necessary. The content of these additives in the heat seal layer is usually 0.01 to 5% by mass for each type of additive.
[0062] The heat seal layer may have a single layer structure or a multi-layer structure. In the case of a multi-layer structure, at least the main component of the outermost surface of the heat seal layer that is bonded to the resin container is selected so as to have the above-mentioned specific combination with the main component of the surface of the resin container.
[0063] <Thickness> From the viewpoint of enhancing adhesiveness, the thickness of the heat seal layer is preferably 0.5 μm or more, more preferably 0.7 μm or more, and even more preferably 1 μm or more. From the viewpoint of suppressing cohesive failure inside the heat seal layer, the thickness of the heat seal layer is preferably 10 μm or less, more preferably 3 μm or less, and even more preferably 2 μm or less. Therefore, the thickness of the heat seal layer is preferably 0.5 to 10 μm, more preferably 0.7 to 3 μm, and even more preferably 1 to 2 μm.
[0064] <Label manufacturing method> The method for producing the label is not particularly limited, but the label can be produced by laminating a base material layer and a heat seal layer film.
[0065] <<Film forming and lamination>> Examples of methods for forming the film of each layer include cast molding in which a molten resin is extruded into a sheet shape using a single-layer or multi-layer T-die, I-die, etc. connected to a screw-type extruder, calendar molding, rolling molding, inflation molding, etc. A film may be formed by casting or calendar molding a mixture of a thermoplastic resin and an organic solvent or oil, and then removing the solvent or oil.
[0066] Examples of film lamination methods include co-extrusion, extrusion lamination, and coating, and these methods can be combined. In the co-extrusion method, resin compositions for each layer melt-kneaded in separate extruders are laminated and extruded in a feed block or multi-manifold, and film formation and lamination are performed in parallel. In the extrusion lamination method, a resin composition is extruded onto a preformed film to laminate the film. In the coating method, a resin solution, emulsion, or dispersion is applied onto a film and dried to form and laminate the film. Among these methods, the co-extrusion method is preferred from the viewpoint of firmly bonding each layer.
[0067] <<Stretching>> The substrate layer or the heat seal layer may be a non-stretched film or a stretched film. Examples of the stretching method include a longitudinal stretching method using the difference in peripheral speed between rolls, a transverse stretching method using a tenter oven, a sequential biaxial stretching method combining these, a rolling method, a simultaneous biaxial stretching method using a combination of a tenter oven and a pantograph, and a simultaneous biaxial stretching method using a combination of a tenter oven and a linear motor, etc. Also usable is a simultaneous biaxial stretching (inflation molding) method in which a molten resin is extruded into a tube shape using a circular die connected to a screw-type extruder, and then air is blown into the extruded resin.
[0068] The substrate layer and the heat seal layer may be stretched individually before lamination of each layer, or may be stretched together after lamination, or the stretched layers may be stretched again after lamination.
[0069] The stretching temperature during stretching is preferably in the range of not less than the glass transition point of the thermoplastic resin used in each layer when the thermoplastic resin is a non-crystalline resin, and is preferably in the range of not less than the glass transition point of the non-crystalline portion of the thermoplastic resin and not more than the melting point of the crystalline portion of the thermoplastic resin when the thermoplastic resin is a crystalline resin.
[0070] The stretching speed is not particularly limited, but from the viewpoint of stable stretch forming, it is preferably within the range of 20 to 350 m / min. The stretching ratio can also be appropriately determined in consideration of the properties of the resin, etc. For example, when a film containing a propylene homopolymer or a copolymer thereof is stretched in one direction, the stretching ratio is usually about 1.2 times or more, preferably 2 times or more, and usually 12 times or less, preferably 10 times or less. When biaxially stretched, the stretching ratio is usually 1.5 times or more, preferably 10 times or more, in terms of area stretching ratio, and usually 60 times or less, preferably 50 times or less. Within the above range of stretching ratio, the desired porosity is easily obtained and opacity is easily improved. In addition, the film is less likely to break and stable stretching tends to be possible.
[0071] <<Print>> A printed layer can be provided on the surface of the base material layer of the label opposite the heat seal layer by printing. Examples of printed information include product information such as product name, logo, manufacturer, distributor name, usage instructions, and barcode. Examples of printing methods include gravure printing, offset printing, flexographic printing, seal printing, and screen printing.
[0072] Furthermore, the printing layer is not limited to printing by the above printing methods, but may also include conventionally known decorations such as printing by various printers, foil stamping such as hot stamping and cold stamping, transfer foil, and holograms.
[0073] <<Label processing>> The label of the present invention can be processed into a required shape and size by cutting or punching. Although cutting or punching can be performed before printing, it is preferable to perform it after printing in terms of ease of operation.
[0074] The thickness of the label is preferably 40 μm or more, more preferably 60 μm or more, from the viewpoint of preventing wrinkles on the label. Also, from the viewpoint of preventing a decrease in strength due to thinning of the container part in which the label is embedded, the thickness is preferably 150 μm or less, more preferably 120 μm or less. Therefore, the thickness of the label is preferably 40 to 200 μm, more preferably 60 to 150 μm.
[0075] [Manufacturing method of labeled containers] The labeled container of the present invention can be produced by in-mold molding a resin container using a mold having a label provided on its inner wall.
[0076] (In-mold molding) The labeled container of the present invention is manufactured by stretch blow molding, which makes it easier to adjust the size of the notch in the resin container. The stretch blow method is a method in which a preform made from a raw resin is heated to near the softening point of the raw resin, and the preform is stretched by a rod in a mold and expanded by applying air pressure to form a container.
[0077] From the viewpoint of embedding the label in the resin container and increasing the depth (d) and width (L) of the notch, the blow pressure in the stretch blow method is preferably 2 MPa or more, more preferably 2.5 MPa or more, and the temperature of the polyester resin in the stretch blow method is preferably 105°C or more, more preferably 110°C or more.
[0078] On the other hand, from the viewpoint of reducing the lengths (d) and (L) of the notch portion, the blow pressure in the stretch blow method is preferably 4 MPa or less, more preferably 3.5 MPa or less, and the polyester resin temperature in the stretch blow method is preferably 130° C. or less, more preferably 120° C. or less. EXAMPLES
[0079] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. In the examples, the terms "parts", "%", and the like are based on mass unless otherwise specified.
[0080] [Raw materials] Table 1 shows a list of raw materials used in the production of labels in the examples and comparative examples. [Table 1]
[0081] [Label manufacturing] <Label manufacturing example 1> 100% by mass of polypropylene (manufactured by Japan Polypropylene Corporation, product name: MA3U, MFR (230°C, 2.16 kg load): 15 g / 10 min) for forming the base layer and 100% by mass of metallocene-based polyethylene (manufactured by Japan Polypropylene Corporation, product name: Kernel KS240T, MFR (190°C, 2.16 kg load): 2.2 g / 10 min, melting point: 60°C) for forming the heat seal layer were melt-kneaded at 240°C using separate extruders.
[0082] The melt-kneaded resins were fed to one co-extrusion T-die, laminated in two layers in the T-die, and extruded from the T-die at 240°C into a sheet. This resulted in a two-layer sheet in which a base layer made of polypropylene and a heat seal layer made of metallocene polyethylene were laminated. This two-layer sheet was guided between a semi-mirror chill roll and a matte rubber roll, and cooled while being pinched (linear pressure of about 1.5 kg / cm). After cutting off the edge, the sheet was wound up by a winder to obtain a polyolefin resin film with a thickness of 90 μm. The obtained film was punched into a rectangle of 8 cm x 6 cm to produce the label of Production Example 1. The total layer thickness of the label of Production Example 1 was 90 μm. In addition, the thickness of the base layer was 87 μm, and the thickness of the heat seal layer was 3 μm.
[0083] <Label manufacturing example 2> 84% by mass of propylene homopolymer (manufactured by Japan Polypropylene Corporation, product name: Novatec PP MA4, MFR (230°C, 2.16 kg load): 5 g / 10 min, melting point: 167°C), 15% by mass of heavy calcium carbonate fine powder (manufactured by Bihoku Funka Kogyo Co., Ltd., product name: Softon #1800, volume average particle size: 1.8 μm), and 1% by mass of rutile titanium dioxide fine powder (manufactured by Ishihara Sangyo Co., Ltd., product name: Typen CR-60, volume average particle size: 0.2 μm) were mixed in a mixer. Next, the mixture was melt-kneaded at 230°C using an extruder to prepare a resin composition for the base layer.
[0084] Meanwhile, 100% by mass of polyethylene (manufactured by Japan Polyethylene Co., Ltd., product name: Kernel KS571, MFR (190°C, 2.16 kg load): 12 g / 10 min, melting point: 100°C) was melted in an extruder heated to 210°C to prepare a resin composition for the heat seal layer.
[0085] The resin compositions of the base material layer and the heat seal layer were fed to a two-layer co-extrusion T-die, laminated in the die, and extruded into a sheet to form a two-layer sheet. The two-layer sheet was cooled by a cooling device to obtain a two-layer non-stretched sheet. The obtained non-stretched sheet was heated to 150°C and stretched 5 times in the longitudinal direction by utilizing the peripheral speed difference between a plurality of roll groups. After cooling to a temperature of 60°C, it was heated again to a temperature of 150°C and stretched 8 times in the transverse direction by using a tenter. After annealing at a temperature of 160°C, it was cooled to a temperature of 60°C to obtain a two-layer white opaque biaxially stretched polyolefin resin film.
[0086] Next, the edge of the biaxially stretched polyolefin resin film was slit, and then the film was wound into a roll by a winding machine. The film was punched into a rectangle of 8 cm x 6 cm to produce the label of Production Example 2. The total layer thickness of the label of Production Example 2 was 95 μm, and the density was 0.76 g / cm. 3 The thickness of the base layer was 92 μm, and the thickness of the heat seal layer was 3 μm.
[0087] <Label manufacturing example 3> A resin composition for the substrate layer was prepared in the same manner as in Label Production Example 2. Furthermore, an ethylene-methyl methacrylate copolymer (manufactured by Sumitomo Chemical Co., Ltd., product name: Acryft WH206-F, MMA content 20 wt%, MFR (230°C, 2.16 kg load): 2 g / 10 min, melting point: 86°C) and a tackifier (manufactured by Harima Chemical Co., Ltd., product name: Haritac SE10, stabilized rosin ester, softening point: 78-87°C, acid value: 2-10 g KOH) were mixed in a weight ratio of 7:3 and melted in an extruder heated to 150°C to prepare a resin composition for the heat seal layer. Each resin composition of the base material layer and the heat seal layer was fed into a two-layer co-extrusion T-die, and in the same manner as in Label Production Example 2, a two-layered, white, opaque, biaxially oriented polyolefin resin film was obtained.
[0088] Next, the edge portion of the biaxially stretched polyolefin resin film was slit, and then the film was wound into a roll by a winding machine. The film was punched into a rectangle of 8 cm x 6 cm to produce the label of Production Example 3. The total layer thickness of the label of Production Example 3 was 95 μm, and the density was 0.77 g / cm. 3 The thickness of the base layer was 93 μm, and the thickness of the heat seal layer was 2 μm.
[0089] <Label manufacturing example 4> The label of Production Example 4 was produced in the same manner as Production Example 2, except that the material of the heat seal layer in Production Example 2 was changed to a mixture of 80% by weight of linear polyethylene (manufactured by Japan Polyethylene Co., Ltd., product name: Novatec LL-UF524, MFR (190°C, 2.16 kg load): 0.9 g / 10 min, melting point 123°C) and 20% by weight of ethylene-vinyl acetate copolymer (EVA) (manufactured by Japan Polyethylene Co., Ltd., Novatec LV440, MFR (230°C, 2.16 kg load): 2 g / 10 min, melting point 89°C).
[0090] <Label manufacturing example 5> The resin compositions of the base material layer and the heat seal layer were prepared in the same manner as in Production Example 1. The resin compositions of the base material layer and the heat seal layer were fed to a two-layer co-extrusion T-die, laminated in the die, and extruded into a sheet to form a two-layer sheet. The two-layer sheet was cooled by a cooling device to obtain a two-layer non-stretched sheet. The obtained non-stretched sheet was heated to 150°C and stretched 5 times in the longitudinal direction by utilizing the peripheral speed difference between a plurality of roll groups. Next, after cooling to a temperature of 60°C, it was heated again to a temperature of 150°C and stretched 8 times in the transverse direction by using a tenter. After annealing at a temperature of 160°C, it was cooled to a temperature of 60°C to obtain a biaxially stretched polyolefin resin film of a two-layer structure.
[0091] Next, the edge of the biaxially stretched polyolefin resin film was slit, and then the film was wound into a roll by a winding machine. The film was punched into a rectangle of 8 cm x 6 cm to produce the label of Production Example 5. The total layer thickness of the label of Production Example 5 was 90 μm, the thickness of the base layer was 87 μm, and the thickness of the heat seal layer was 3 μm.
[0092] <Label manufacturing example 6> The material for the base layer was prepared in the same manner as in Production Example 1, and the material for the heat seal layer was prepared in the same manner as in Production Example 4. The resin compositions for the base layer and the heat seal layer were fed to a two-layer co-extrusion T-die, laminated in the die, and extruded into a sheet to form a two-layer sheet. This two-layer sheet was cooled by a cooling device to obtain a two-layer non-stretched sheet. The obtained non-stretched sheet was heated to 150°C and stretched 5 times in the longitudinal direction using the peripheral speed difference between a plurality of roll groups. Next, after cooling to a temperature of 60°C, it was heated again to a temperature of 150°C and stretched 8 times in the transverse direction using a tenter. After annealing at a temperature of 160°C, it was cooled to a temperature of 60°C to obtain a biaxially stretched polyolefin resin film with a two-layer structure.
[0093] Next, the edge of the biaxially stretched polyolefin resin film was slit, and then the film was wound into a roll by a winding machine. The film was punched into a rectangle of 8 cm x 6 cm to produce the label of Production Example 6. The total layer thickness of the label of Production Example 6 was 90 μm, the thickness of the base layer was 87 μm, and the thickness of the heat seal layer was 3 μm.
[0094] <Label manufacturing example 7> The material of the base layer was prepared in the same manner as in Production Example 2, and the resin composition of the heat seal layer was prepared in the same manner as in Production Example 1. The resin compositions of the base layer and the heat seal layer were fed to a two-layer co-extrusion T-die, laminated in the die, and extruded into a sheet to form a two-layer sheet. This two-layer sheet was cooled by a cooling device to obtain a two-layer non-stretched sheet. The obtained non-stretched sheet was heated to 150°C and stretched 5 times in the longitudinal direction using the peripheral speed difference between a plurality of roll groups. Next, after cooling to a temperature of 60°C, it was heated again to a temperature of 150°C and stretched 8 times in the transverse direction using a tenter. After annealing at a temperature of 160°C, it was cooled to a temperature of 60°C to obtain a two-layer white opaque biaxially stretched polyolefin resin film.
[0095] Next, the edge of the biaxially stretched polyolefin resin film was slit, and then the film was wound into a roll by a winding machine. The film was punched into a rectangle of 8 cm x 6 cm to produce the label of Production Example 7. The total layer thickness of the label of Production Example 7 was 90 μm, the thickness of the base layer was 87 μm, and the thickness of the heat seal layer was 3 μm.
[0096] <Label manufacturing example 8> Except for changing the thickness of the heat seal layer, a label was produced in the same manner as in Production Example 1. The total layer thickness of the label in Production Example 1 was 90 μm. The thickness of the base layer was 75 μm, and the thickness of the heat seal layer was 15 μm.
[0097] [Manufacturing labeled containers] <Example 1> The label of Production Example 1 was charged with an electrostatic charging device, and then fixed inside the molding die of a stretch blow molding machine (manufactured by Nissei ASB Co., Ltd., machine name: ASB-70DPH) and clamped. At this time, the label was fixed by suction so that the base layer of the label was in contact with the cavity of the die. In addition, the temperature of the die was controlled with circulating water so that the surface temperature of the cavity side of the die was 45°C.
[0098] On the other hand, a preform made of polyethylene terephthalate (PET) resin (manufactured by Nippon Unipet Co., Ltd., product name: Unipet RD383, melting point 235°C) was preheated to 110°C. Next, the preform was introduced into a mold and stretch-blow molded by applying a blow pressure of 3 MPa for 1 second. After cooling to 50°C in 15 seconds, the mold was opened to obtain a labeled container.
[0099] <Examples 2 to 5> Labeled containers were obtained in the same manner as in Example 1, except that the labels of Production Examples 5 to 8 were used.
[0100] <Comparative Example 1> A labeled container of Comparative Example 1 was produced in the same manner as in Example 1, except that the label of Production Example 1 in Example 1 was changed to the label of Production Example 3.
[0101] <Comparative Example 2> The label of Production Example 4 was fixed by suction to one of the split molds for direct blow molding so that the surface layer side was in contact with the mold. Then, polyethylene terephthalate (manufactured by Nippon Unipet Co., Ltd., trade name: Unipet RD383, melting point 235°C) was melt-extruded at 260°C to form a parison. After this parison was introduced between the split molds, the split molds were clamped, and air at a pressure of 0.5 MPa was supplied into the parison to obtain a labeled container of Comparative Example 2. At this time, the mold was temperature-controlled with circulating water so that the surface temperature of the cavity side of the mold was 15°C.
[0102] <Comparative Example 3> In Comparative Example 2, high density polyethylene (HDPE) (product name: Novatec HDHB330, manufactured by Japan Polyethylene Co., Ltd., melting point 133°C) was melt extruded at 220°C instead of polyethylene terephthalate (PET) resin to form a parison, the blow pressure was changed to 0.4 MPa, the cavity side surface temperature of the mold was changed to 10°C, and the label of Production Example 2 was used instead of the label of Production Example 4, but the labeled container of Comparative Example 3 was obtained in the same manner as in Comparative Example 2.
[0103] [Evaluation method] <Measurement of the size of the notch of a resin container> Each labeled container of the Examples and Comparative Examples was cut from above the label with a cutter knife, and two samples for observation were prepared from each labeled container. In order to select an area that was less affected by stretching during the manufacture of the labeled container, an area including one side close to the mouth of the container was cut out.
[0104] <<Measurement of depth (d)>> The prepared sample was observed with an optical microscope to search for the notch around the label. In the observed image, as shown in FIG. 2, an intersection P1 between the inclined surface K1 of the resin container 1 forming the notch 11 and the end surface of the label 2 was identified. In addition, an intersection P2 between a line K3 including this intersection P1 and extending in the thickness direction of the label 2 and a line K4 extending along the surface of the resin container 1 to which the label is not attached was identified. Next, the distance between the intersection P1 and the intersection P2 was measured. The measurement was performed twice by changing the observation position, and the average of the measured values was taken as the measured value of the depth d of the notch [μm].
[0105] <<Measurement of width (L)>> Next, in the observed image, the intersection point P3 between the line K4 and the inclined surface K1 was identified as shown in Figure 2. Then, the distance between the intersection points P2 and P3 was measured. The measurement was performed twice by changing the observation position, and the average of the measured values was taken as the measured value of the width L of the notch portion [μm].
[0106] <Embedding rate> The label embedment rate (%) was calculated using the above formula (F1) from the thickness t (μm) of each label (if the label protruded from the surface of the resin container, the thickness of the label excluding the protruding part) and the measured depth d (μm) of the notch.
[0107] <Trigger for peeling> The surface of the resin container with the label was scratched with a fingernail from the periphery of the label toward the label. The trigger for the label to peel off was evaluated as follows. Excellent: Fingernails easily get caught in the notch between the resin container and the label Good: Fingernails easily get caught in the notch between the resin container and the label Fair: Your fingernail gets caught in the notch between the resin container and the label. Poor: No nails catch
[0108] <Easy to peel off> The ease of peeling off the labels from the labeled containers was evaluated as follows. A fingernail was used to peel off a portion of the label on a labeled container, up to 10 mm in length. This peeled portion was connected to a digital force gauge (IMADA Corporation, DST-20N) and a peeling force was applied to the peeled portion to remove the label.
[0109] The ease of peeling the label was evaluated as follows based on the peel force required to peel off the entire label: If the peel force exceeds 10 kN, it is difficult to peel off the label by hand. Excellent: Peeling force is 4kN or less Good: Peeling force is 4kN or more and 10kN or less Poor: Peeling force exceeds 10kN
[0110] <Adhesiveness> The labeled portion of the labeled container was grasped by hand and squeezed (deformed) 10 times. After that, the label was observed for lifting or falling off, and the adhesiveness of the label on the labeled container was evaluated as follows. Excellent: The label did not lift or fall off after 10 squeezes, and the adhesiveness is sufficient for practical use. Good: No lifting or falling off of the label was observed after 5 squeezes, but lifting or falling off of the label was observed after 10 squeezes, and the adhesiveness was sufficient for practical use. Poor: Label lifting or falling off was observed after 5 squeezes, and the adhesiveness was not practical.
[0111] The evaluation results are shown in Table 2 below. In the molding methods in Table 2, ISBM (Injection stretch blow molding) represents the stretch blow method, and EBM (Extrusion blow molding) represents the direct blow method. [Table 2]
[0112] As shown in Table 2, Example 1, which has a notch of a predetermined size, has adhesiveness that is practical and easy to peel off. Example 1 has a notch of a predetermined size, and the heat seal layer and the resin container are made of a combination of polyethylene resin and polyester resin as the main components, so that the ease of peeling is also good.
[0113] On the other hand, in Comparative Examples 1 and 3, the resin having a polar group in a part thereof or the same type of resin is used in the heat seal layer as in the resin container, so the adhesiveness is high, but it is too high and difficult to peel off. In addition, in Comparative Examples 2 and 3, the notch part of the resin container does not reach the predetermined size, so it is difficult to create an opportunity for peeling.
[0114] This application claims priority to Japanese Patent Application No. 2021-38366, filed on March 10, 2021, and incorporates by reference all of the contents of that Japanese Patent Application. [Explanation of symbols]
[0115] 10...container with label, 1...resin container, 11...notch portion, 2...label, 2a...tab portion, 21...base material layer, 22...heat seal layer
Claims
1. A labeled container comprising a label having a heat seal layer and a resin container to which the label is adhered via the heat seal layer, A part of the label is embedded in the resin container, and a notch is provided around the label. The depth (d) of the notch is 40 μm or more, The width (L) of the notch portion is 300 μm or more, One of the resin container and the heat seal layer at the adhesive surface contains a polyolefin resin as a main component, and the other contains a polyester resin as a main component. Labeled container.
2. The depth (d) of the notch is 100 μm or less.
2. The labeled container of claim 1.
3. The width (L) of the notch is 900 μm or less.
3. A container with a label according to claim 1 or 2.
4. The heat seal layer contains a polyolefin resin as a main component, The resin container contains a polyester resin as a main component. A container with a label according to any one of claims 1 to 3.
5. The label includes a base layer on a surface of the heat seal layer opposite the resin container, The substrate layer is a porous resin film containing a thermoplastic resin and a filler. A container with a label according to any one of claims 1 to 4.
6. 6. A labeled container according to claim 1, wherein the embedment rate of the label in the resin container calculated by the following formula (F1) is 3% or more and 50% or less. (F1) Embedding rate (%) = (t-d) x 100 / t [In formula (F1), t represents the thickness of the label, and d represents the depth of the notch.]
7. A labeled container described in any one of claims 1 to 6, wherein the polyolefin resin comprises at least one resin selected from the group consisting of ethylene-based resins, propylene-based resins, ethylene-propylene copolymers, and ethylene-α-olefin copolymers.
8. A labeled container described in any one of claims 1 to 7, wherein the heat seal layer further contains a resin having an olefin and a monomer having a polar group other than an olefin as polymerization components.
Citation Information
Patent Citations
Label bonding method for hollow molded container
JP1995100906A
Blow bottle
JP2000247334A
Labelled in-mold molded product and in-mold label
JP2006168355A
Labelled in-mold molding
JP2008133006A
Label for in-mold molding and molded article with the label
JP2009040038A